Orthopedic treatment of Class III malocclusion with rapid maxillary expansion combined with a face mask: a cephalometric assessment of craniofacial growth patterns - Daniella Torres Tagawa; Carolina Loyo Sérvulo da Cunha Bertoni; Maria Angélica Estrada Mari; Milton Redivo Junior; Luís Antônio de Arruda Aidar (Dental Press Editora, 2012)
OBJECTIVE: The aim of this prospective study was to assess potential changes in the cephalometric craniofacial growth pattern of 17 children presenting Angle Class III malocclusion treated with a Haas-type expander combined with a face mask. METHODS: Lateral cephalometric radiographs were taken at beginning (T1) and immediately after removal of the appliances (T2), average of 11 months of treatment. Linear and angular measurements were used to evaluate the cranial base, dentoskeletal changes and facial growth pattern. RESULTS: The length of the anterior cranial base experienced a reduction while the posterior cranial base assumed a more vertical position at T1. Some maxillary movement occurred, there was no rotation of the palatal plane, there was a slight clockwise rotation of the mandible, although not significant. The ANB angle increased, thereby improving the relationship between the jaws; dentoalveolar compensation was more evident in the lower incisors. Five out of 12 cases (29.41%) showed the following changes: In one case the pattern became more horizontal and in four cases more vertical. CONCLUSIONS: It was concluded after a short-term assessment that treatment with rapid maxillary expansion (RME) associated with a face mask was effective in the correction of Class III malocclusion despite the changes in facial growth pattern observed in a few cases.